Association Between Prevalence of Peripheral Artery Disease and Radiation Exposure in the Atomic Bomb Survivors. Issue 23 (4th December 2018) - Takahashi, Ikuno; Cologne, John; Haruta, Daisuke; Yamada, Michiko; Takahashi, Tetsuya; Misumi, Munechika; Fujiwara, Saeko; Matsumoto, Masayasu; Kihara, Yasuki; Hida, Ayumi; Ohishi, Waka
Abstract : Background: Past reports suggested that total‐body irradiation at 0.5 to 1.0 Gy could be responsible for atherosclerosis. Peripheral artery disease (PAD) is a manifestation of systematic atherosclerosis. Whether the consequences of a low‐to‐moderate dose of radiation include increased risk of PAD remains to be determined. The purpose of this study was to examine the association between radiation exposure and prevalence of PAD among Japanese atomic bomb survivors. Methods and Results: Radiation exposure from the atomic bombing was assessed in 3476 participants (41.1% men, mean age 74.8 years with SD 6.4 years) with a cross‐sectional survey in 2010 to 2014. Left‐ and right‐side ankle‐brachial indexes and upstroke time (UT) were obtained using oscillometric VP‐2000. PAD was defined as an ankle‐brachial index of 1.0 or less or a prior history related to revascularization. UT was considered a sensitive marker of early‐stage PAD. Association between radiation exposure and PAD or UT was assessed using multivariable regression analyses with adjustment for potential confounding factors. Of 3476 participants, 79 (2.3%) were identified as having prevalent PAD. Multivariate logistic regression analysis indicated that radiation dose was unrelated to PAD prevalence (odds ratio, 0.83; 95% confidence interval [0.57‐1.21]). UT appeared to increase with radiation dose, but the increase was not statistically significant (1.09 ms/Gy; 95% confidence interval [−0.17 to 2.36]). Conclusions: We found no clear association of radiation dose with PAD, but it remains to be determined whether UT is associated with radiation dose.